2013
DOI: 10.1016/j.toxlet.2013.02.015
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of waterpipe smoke condensate on endothelial cell function: A potential risk factor for vascular disease

Abstract: Aim Despite its increasing popularity, little is known about the health effects of waterpipe smoking (WPS), particularly on the cardiovascular system. To investigate the role of WPS as a risk factor for vascular disease, we evaluated its effect on endothelial cell function, which is an early event in vascular disease pathogenesis. We assessed the changes in cell viability, ROS generation, inflammatory and vasodilatory markers and in vitro angiogenesis of human aortic endothelial cells in response to waterpipe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…On the other hand, previously reported higher benzene and carcinogenic PAHs from water pipe smoking suggest that the health risks associated with these toxicants are likely higher among water pipe smokers than nonsmokers with secondhand cigarette smoke exposure or even among light and intermittent cigarette smokers. In vitro studies show that water pipe smoke causes DNA damage, has cytotoxic and mutagenic effects, and causes endothelial dysfunction (49-51). Water pipe smoking compromised cardiac autonomic function in a clinical study (52).…”
Section: Nicotine Intakementioning
confidence: 99%
“…On the other hand, previously reported higher benzene and carcinogenic PAHs from water pipe smoking suggest that the health risks associated with these toxicants are likely higher among water pipe smokers than nonsmokers with secondhand cigarette smoke exposure or even among light and intermittent cigarette smokers. In vitro studies show that water pipe smoke causes DNA damage, has cytotoxic and mutagenic effects, and causes endothelial dysfunction (49-51). Water pipe smoking compromised cardiac autonomic function in a clinical study (52).…”
Section: Nicotine Intakementioning
confidence: 99%
“…There is a general misperception that this method of inhaling burnt tobacco is less harmful, 4,5 despite the high concentration and large volume of carbon monoxide generated. [6][7][8][9] Narghile's effect on the cardiovascular system is evident in causing endothelial cell dysfunction, 10 in decreasing heart rate variability, and in increasing blood pressure and heart rate. 11 Narghile smoking was found to increase nicotine concentration in the blood, 12 a finding that can explain its association with dependence.…”
mentioning
confidence: 99%
“…Using a pretest and post-test design, Hawari et al 54 found that acute hookah smoking impaired lung function and exercise capacity by increasing CO levels, respiratory rate and systolic blood pressure, as well as decreasing oxygen consumption and forced expiratory flow. In addition, in vitro studies have demonstrated the ability of tobacco-based hookah smoke condensate to induce endothelial cell dysfunction by exerting oxidative stress, inflammation and impaired endothelial vasodilatory function and repair mechanisms 45 55. No studies to date, however, have explored the potential long term dangers to employees working in hookah bars who are exposed for extended periods of time.…”
Section: Discussionmentioning
confidence: 99%